2014
DOI: 10.1002/anie.201408826
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)‐Catalyzed Three‐Component Reaction of Terminal Propargyl Alcohols, Aldehydes, and Amines: Synthesis of 3‐Amino‐2‐pyrones and 2,5‐Dihydrofurans

Abstract: A novel copper(I)-catalyzed three-component reaction for the efficient synthesis of 3-amino-2-pyrones and 2,5-dihydrofurans from propargyl alcohols, aldehydes, and amines has been developed. The starting materials are easily available and the scope of this method is broad. Through mechanistic studies, it is believed that the three-component reaction consists of an A(3) -coupling to propargylic amine, alkyne-allene isomerization, and intramolecular cyclization of the allenol to form a furan. In case of using et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
0
12
0
1
Order By: Relevance
“…A novel copper(I)‐catalyzed three‐component protocol for the efficient and selective synthesis of 3‐amino‐2‐pyrones 101 and 2,5‐dihydrofurans 102 (Scheme ) from the coupling of propargyl alcohols 100 , aldehydes 1 , and amines 2 has been developed by Ma et al The reaction was expected to proceed through the synthesis of propargylamine 102I , which on alkyne–allene isomerization, followed by an intramolecular cyclization of the allenol 102Ia provided furan 102 . Interestingly, in case of utilizing ethyl glyoxalate (R 1 = COOEt) as the aldehyde part, furan further underwent a ring‐opening, then lactonization ( 101I ), and isomerization to afford 3‐amino‐2‐pyrones 101 (Scheme ).…”
Section: Synthetic Utility Of A3 Coupling Reactionsmentioning
confidence: 99%
“…A novel copper(I)‐catalyzed three‐component protocol for the efficient and selective synthesis of 3‐amino‐2‐pyrones 101 and 2,5‐dihydrofurans 102 (Scheme ) from the coupling of propargyl alcohols 100 , aldehydes 1 , and amines 2 has been developed by Ma et al The reaction was expected to proceed through the synthesis of propargylamine 102I , which on alkyne–allene isomerization, followed by an intramolecular cyclization of the allenol 102Ia provided furan 102 . Interestingly, in case of utilizing ethyl glyoxalate (R 1 = COOEt) as the aldehyde part, furan further underwent a ring‐opening, then lactonization ( 101I ), and isomerization to afford 3‐amino‐2‐pyrones 101 (Scheme ).…”
Section: Synthetic Utility Of A3 Coupling Reactionsmentioning
confidence: 99%
“…A novel Cu(I)‐catalysed three‐component reaction for the synthesis of 3‐amino‐2‐pyrones and 2,5‐dihydrofurans has been reported from aldehydes, propargyl alcohols and amines (Scheme ) . The optimized conditions were identified as CuBr as catalyst in 1,4‐dioxane at 40 °C.…”
Section: Synthesis Of Heterocyclesmentioning
confidence: 99%
“…Exploring Cu-catalyzed three-component coupling of terminal alkynes, aldehydes, and amines, Fan and Ma 61 observed the formation of an unexpected cyclized pyrone derivative as a minor product in reactions utilizing ethyl glyoxylate, along with a secondary amine and a terminal unprotected propargyl alcohol. An optimized protocol involving a CuBr-catalyzed coupling of terminal propargyl alcohols, ethyl glyoxylate, and secondary amines in 1,4dioxane followed by the treatment of the crude product with silica in toluene afforded an extensive series of 3-amino-2pyrone derivatives.…”
Section: Transition Metal-catalyzed Mcrs In Sequential Protocolsmentioning
confidence: 99%
“…The products were diversified at the C-6 positions by the variation of the substituent (R 1 ) on the propargyl alcohol, and featured diverse substituents (R 2 ) on the nitrogen, reflecting the choice of the secondary amine component (reaction A; Figure 9). 61 A mechanistic study indicated that a 2,5-dihydrofurane derivative B could be isolated prior to treatment with silica. Presumably, the amino propargyl amine/alcohol A (Figure 9) that results from the initial MCR, undergoes an alkyne-to-allene isomerization prior to the cyclization to yield the pyrones.…”
Section: Transition Metal-catalyzed Mcrs In Sequential Protocolsmentioning
confidence: 99%
See 1 more Smart Citation